Local policy for managing the risk of the proliferation and spread of Legionella in the Girona area. (30th September 2020) - Vilà, I; Esparraguera, C; Arjona, L; Castro, P; Redondo, M; Soms, D; Macau, A; del Acebo, X
Abstract: Issue: The towns in the Girona area are mostly small (70% have fewer than 1.500 inhabitants) and employ few public health technicians. Difficulties exist in municipal facilities when it comes to carrying out self-assessment tests and fulfilling regulatory requirements. Description: In 2009, Dipsalut designed a programme to offer support to local councils in the management and control of the sanitation of municipal facilities at risk of transmitting Legionella. Main Objectives: To improve the control of the health risk, to ensure the technical capacitation of personnel and to achieve territorial equity in health protection. The programme methodology comprised: a service provision programme with structured actions, a network of public health stakeholders and an information system shared between the stakeholders. The programme includes the structural description of the facilities, the study of the risk factors for the proliferation and spread of Legionella, the drawing up of control plans based on the HACCP system, analyses to determine and quantify Legionella, preventive cleaning and disinfection, on-site advice for workers, and training courses. Results: Regarding the improvement in the control of the health risk: - In 2019, 905 facilities were controlled in 105 towns. In the last 8 years, the refurbishment of 239 facilities has been carried out, involving a total investment of 2, 075.857€. Reduction in the concentration of Legionella where more exhaustive sampling is carried out. Regarding the technical capacitation of personnel: 2.012 people on courses and 10.121 people in visits on-site. Lessons: Realising the importance of ensuring the co-responsibility of facility managers. Adapting actions to be carried out in facilities according to risk: the greater the risk, the greater the effort. Key messages: The application of an area-wide programme improves facility risk management. Ensuring technical capacitation, incorporating improvements based on common experiences and optimising resources.